Pengembangan Strategi Pemasaran Digital untuk Meningkatkan Visibilitas Bagi Komunitas Relawan Gemar Sedekah - Aditya Eko Adrianto; Wahid Tuftazani Rizqi; Yohanes De Britto Wirajati (Abdi Seni, 2025)
In the rapidly evolving digital era, the use of digital marketing strategies has become an urgent necessity for social institutions such as Relawan Gemar Sedekah to enhance visibility and donation support. By employing an approach that integrates fine art elements, this community engagement initiative aims to implement effective digital marketing strategies to improve public understanding of the institution's mission and values, as well as to motivate society to participate in charitable activities. By analyzing public perception and responses toward fine art-based content presented in digital marketing campaigns, this initiative can develop more impactful and measurable strategies. The targeted outcomes include the development of a practical guide for digital marketing using a fine art approach, increased online visibility for Relawan Gemar Sedekah, and a rise in the number and frequency of donations received. Therefore, it is expected that this initiative will contribute significantly to strengthening the position of social institutions in an increasingly complex and competitive digital landscape, while also amplifying their positive impact in aiding those in need of assistance. Keywords: Digital marketing, fine arts, strategy, contribution, visibility